Do Differences in Livestock Management Practices Influence Environmental Impacts? - Kleppel, Gary S. (Frontiers in Sustainable Food Systems, 2020)
Herbivore-carnivore interactions have been fundamental to grassland ecosystem functionality and to the human cultures that have long depended on these ecosystems for their nutrition. However, a large literature has developed during the past century indicating that animal agriculture is responsible for numerous negative environmental impacts. In this paper, I review literature on some of the environmental impacts of two different livestock management approaches, industrial-conventional (IC) management and regenerative-multi-paddock (RM) management. I consider the null hypothesis that the environmental impacts of ruminant livestock production are independent of the approach used to manage animals and grazing lands. It evident in the literature that managed grazing ecosystems are complex, and for certain system attributes, such forage quality and community structure, determination of the better management system is difficult to discern. It is, furthermore, unclear whether more research will produce a more definitive answer. In other areas resolution was clearer. For instance, it would appear that the soils of RM grasslands exhibit higher microbial biomass and diversity, and higher fungal: bacterial ratios than IC soils. Several impacts associated with livestock production appear to have less to do with grazing, per se, and more to do with support factors, most notably feed production. Data from several sources suggest that changes in feed production use factors by pasture-based (RM) management may reduce blue withdrawals by >50% and GHG emissions by approximately 28% relative to conventional production. Life cycle assessment reveals that RM livestock finishing tends to be carbon negative due to high C-sequestration rates associated with grazing-land management, while IC finishing represents a substantial carbon source. Accumulating data suggest that a significant portion of the CO2-eq can be removed from the atmosphere and stored in the soil by applying RM management practices. While research design may affect the outcome of some studies, the quality and quantity of the science may not resolve discrepancies in the data. It is suggested that the viability and sustainability of animal agriculture may depend on broadening the goals of practitioners to include both food production and the maintenance of environmental health.